2010
DOI: 10.18388/abp.2010_2448
|View full text |Cite
|
Sign up to set email alerts
|

Adult-type hypolactasia and lactose malabsorption in Poland.

Abstract: The available data on the incidence of lactose malabsorption are contradictory. Potential bias in random selection is a major drawback of studies performed to-date. Moreover, molecular analysis of polymorphism -13910 C>T upstream of the lactase (LCT) gene (NM_005915.4:c.1917+326C>T; rs4988235) has not been reported in those studies. Therefore, in this study we aimed to assess genetic predisposition and clinical manifestation of adult-type hypolactasia (ATH). In two-hundred randomly chosen healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
(28 reference statements)
2
16
0
1
Order By: Relevance
“…Whilst in the human population, sucrase and maltase show consistent activity that of lactase varies depending on several factors, for example the age. These facts have been confirmed by the previously undertaken studies, in which differences in lactase activity were verified while in the case of sucrase and maltase consistent values were detected (Grundmann et al, 2011;Vieira et al, 2000;Mądry et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Whilst in the human population, sucrase and maltase show consistent activity that of lactase varies depending on several factors, for example the age. These facts have been confirmed by the previously undertaken studies, in which differences in lactase activity were verified while in the case of sucrase and maltase consistent values were detected (Grundmann et al, 2011;Vieira et al, 2000;Mądry et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…In several Polish studies, the incidence of the LCT-13910CC genotype associated with ATH in healthy people was estimated at 30-31.5% [7, 17], which was a comparable incidence to that obtained in the whole group of patients with IBD (31%), while slightly less than that in the group of children with AP-FGID (42.4%); the difference was not significant. In all patients, the presence of LCT-13910CC and LCT-22018GG genotypes was consistent.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, it was proven that the genotypes of both variants exhibit almost complete compliance; patients with the LCT-13910CC genotype also had the LCT-22018GG genotype, and patients with the LCT-13910TT genotype has the LCT-22018AA genotype [3]. In Poland, the incidence of lactose malabsorption (LM), assessed by the hydrogen breath test, varies from 17.4 to 37.5%, while the incidence of the LCT-13910CC genotype responsible for ATH was estimated at 30-31.5% [57]. Typical symptoms of lactose intolerance (LI) are diarrhoea, bloating, abdominal pain, nausea, and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSION Studies in the Caucasian populations [7,[19][20][21] showed a high correlation between lactose digestion, intestinal lactase levels, and genetic tests in individuals with different SNP MCM6 genotypes.…”
Section: Resultsmentioning
confidence: 95%